Orbital cellulitis secondary to sinusitis. Case presentation - Oslaymi Yero Lorente; Miriellis Rodriguez Benítez; Manuel Enrique Rodríguez Valdés; Yelenis Abreu Jáuregui (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Orbital cellulitis is the most frequent cause of acute swelling of the orbit and is a relatively frequent ophthalmological emergency and potentially serious in the pediatric population. The inflammation may extend to post septal region, and affect the orbit content. The anatomical relation of the orbit with their neighboring structures as paranasal sinuses is the key to understand the etiopathogenesis of the disease; a case of a five-year-old patient is presented, with a diagnosis of orbital cellulitis secondary to sinusitis. The description of the clinical characteristics of the disease and its management in this case, may offer useful information for a better approach of this entity. It is concluded that the main elements are early diagnosis and multidisciplinary evaluation.